Dynamic properties of transcriptional condensates modulate CRISPRa-mediated gene activation - Yujuan Fu; Xiaoxuan Yang; Sihui Li; Chenyang Ma; Yao An; Tao Cheng; Ying Liang; Shengbai Sun; Tianyi Cheng; Yongyang Zhao; Jianghu Wang; Xiaoyue Wang; et al. (Nature Communications)
Abstract CRISPR activation (CRISPRa) is a powerful tool for endogenous gene activation, yet the mechanisms underlying its optimal transcriptional activation remain unclear. By monitoring real-time transcriptional bursts, we find that CRISPRa modulates both burst duration and amplitude. Our quantitative imaging reveals that CRISPR-SunTag activators, with three tandem VP64-p65-Rta (VPR), form liquid-like transcriptional condensates and exhibit high activation potency. Although visible CRISPRa condensates are associated with some RNA bursts, the overall levels of phase separation do not correlate with transcriptional bursting or activation strength in individual cells. When the number of SunTag scaffolds is increased to 10 or more, solid-like condensates form, sequestering co-activators such as p300 and MED1. These condensates display low dynamicity and liquidity, resulting in ineffective gene activation. Overall, our studies characterize various phase-separated CRISPRa systems for gene activation, highlighting the foundational principles for engineering CRISPR-based programmable synthetic condensates with appropriate properties to effectively modulate gene expression.